2019
DOI: 10.1016/j.proci.2018.06.195
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the auto-ignition of a transient propane Jet-in-Hot-Coflow

Abstract: Auto-ignition is a complex process which is extremely sensitive to boundary conditions such as local temperature, mixture or strain rate and occurs on very short timescales. Therefore, measurement techniques with high spatio-temporal resolution have to be applied to test cases with well-defined boundary conditions in order to generate high-quality validation data for numerical simulations. In the current paper, the auto-ignition of a transient propane jet-in-hot coflow was studied with high-speed OH* chemilumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Following calibration and estimation of the gas composition, this can provide the local number of molecules per unit volume (number density, n) and, hence, local temperature based on the ideal gas law. In non-reacting flows, results from this method can be accurate to within 1% (Arndt et al, 2019).…”
Section: Principles Of Light-matter Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Following calibration and estimation of the gas composition, this can provide the local number of molecules per unit volume (number density, n) and, hence, local temperature based on the ideal gas law. In non-reacting flows, results from this method can be accurate to within 1% (Arndt et al, 2019).…”
Section: Principles Of Light-matter Interactionsmentioning
confidence: 97%
“…The occurrence of these structures is largely dependent on the combination of fuel/oxidant composition and temperatures (Medwell et al, 2008(Medwell et al, , 2016Medwell and Dally, 2012a;Evans et al, 2016a,b), which dictates both the stoichiometric and most-reactive mixture fractions, and the underlying flow-field, which governs the local strain-field between the fuel and oxidant streams (Ye et al, 2016). Of these mechanisms, ignition kernel formation and autoignitive triple flames have been examined at significant length, and a full discussion is not provided here (Gordon et al, 2008;Mastorakos, 2009;Yoo et al, 2011;Arndt et al, 2012Arndt et al, , 2019Sidey and Mastorakos, 2015;Macfarlane et al, 2017Macfarlane et al, , 2018Macfarlane et al, , 2019Ramachandran et al, 2019). Observations from OH-PLIF (Medwell et al, 2008), and resulting numerical studies (Medwell et al, 2009b;Evans et al, 2016bEvans et al, , 2017a suggest that the least studied of these mechanisms-the "weak-to-strong transition"anchors as a weakly reacting diffusion flame close to the jet exit, in ≈ 0.2 (Evans et al, 2016a) under temperature and flowfield conditions almost identical to the laminar coflow stream.…”
Section: Reaction-zone Imaging In Understanding Flame Stabilizationmentioning
confidence: 99%
“…The auto-ignition experiment, which is the subject of the investigations in the present work, has been conducted by Arndt et al [7,9] on the "DLR (Deutsches Zentrum für Luft-und Raumfahrt (Germany Aerospace Center)) JHC (jet in hot coflow)" burner [4,6]. In this experiment, the auto-ignition of a methane jet in a coflow of hot, vitiated air is investigated.…”
Section: Description Of Experimental Setupmentioning
confidence: 99%
“…So far, quantitative scalar measurements with high spatio-temporal resolution in Jet-in-Hot-Coflow flames are limited to temperature and mixture fraction. Arndt et al and Papageorge et al studied the formation of ignition kernels in a jet-in-hot-coflow (JHC) burner developed at the German Aerospace Center (DLR), the DLR JHC, using planar laser Rayleigh-scattering at a pulse repetition rate of 10 kHz for different fuels [30][31][32]. It was found that the scalar dissipation rate plays a key role in determining the ignition time and location.…”
Section: Introductionmentioning
confidence: 99%